2021
DOI: 10.30650/ajte.v3i2.2194
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception on the Effect of Online Learning During Covid 19

Abstract: The educational system across the world has been affected due to outbreak of Covid-19 pandemic, this new phenomenon forced teachers and students to do teaching and learning process from home. The purpose of writing this study was to investigate the students' perceptions of online learning has been implemented and the factors that influenced these perceptions. Therefore, this survey asked 60 students in Sekolah Tinggi Teknologi Migas Balikpapan to convey their perception on the effect of online during Covid-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…Due to poor internet connection, some projects were submitted late. Unfortunately, the issue of poor internet connectivity and data is not unusual in Indonesia as reported in previous studies (see, e.g., Inawati and Setyowati, 2020;Nur Agung et al, 2020;Prasojo & Srisudarso, 2021;Yanti, 2021) The issue of plagiarism was the next hurdle for the PjBL implementation reported in this paper. To address this issue, the writing lecturer instructed students to check the originality of their work using a plagiarism checker available for free online and to submit their writing product together with the originality check result.…”
Section: Project Reflectionmentioning
confidence: 55%
“…Due to poor internet connection, some projects were submitted late. Unfortunately, the issue of poor internet connectivity and data is not unusual in Indonesia as reported in previous studies (see, e.g., Inawati and Setyowati, 2020;Nur Agung et al, 2020;Prasojo & Srisudarso, 2021;Yanti, 2021) The issue of plagiarism was the next hurdle for the PjBL implementation reported in this paper. To address this issue, the writing lecturer instructed students to check the originality of their work using a plagiarism checker available for free online and to submit their writing product together with the originality check result.…”
Section: Project Reflectionmentioning
confidence: 55%
“…Other studies also suggest that cooperative learning significantly influences students’ social development (Johnson et al, 2014; Lou et al, 2006; Yanti, 2021), interactions with other group members, and their respect for the assignment contributions of others (Gillies, 2016). Moreover, studies show that cooperative learning in an EFL classroom improves students’ working relationships, class involvement, achievement (Gillies, 2016; Yanti, 2021), solidarity, respect and tolerance (Rabi’ah et al, 2021). Similarly, a study conducted by Neo et al (2012) showed that students who engaged in cooperative learning recognized the need for respect, communication, sharing, and tolerance as essential components of collaboration and the project’s success.…”
Section: Discussionmentioning
confidence: 99%
“…It means that, the condition of teaching from teacher was conducive. The condition in online learning should be arranged well in order to teach effectively (Yanti: 2021) Diagram 4. The percentages of "A conducive condition during online learning is when the teacher delivers the material"…”
Section: The Teacher Explains the English Phonology Materials Well Th...mentioning
confidence: 99%
“…Several research are done by researchers about online learning in the covid-19 pandemic (Yanti, 2021;Rifiyanti, 2020;Susila, 2020;Ismanto, et al, 2017;Maknuni 2020;Yunus and Fransiska 2020;Wilson 2020). The research findings reported very valuable inputs to manage the better teaching in the future for choosing the wise way of teaching, finding the material, choosing the suitable sources, and getting active in online classroom.…”
Section: Introductionmentioning
confidence: 99%